2013
DOI: 10.1111/cei.12030
|View full text |Cite
|
Sign up to set email alerts
|

The PTPN22 1858T allele but not variants in the proximal promoter region ofIL-21gene is associated with the susceptibility to type 1 diabetes and the presence of autoantibodies in a Brazilian cohort

Abstract: Patients with T1AD had increased frequencies of anti-islet-cell, anti-thyroid, anti-nuclear, anti-smooth muscle and anti-21-OH autoantibodies. The C1858T PTPN22 polymorphism was also associated with a higher frequency of GAD65 and TG autoantibodies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 39 publications
0
5
0
2
Order By: Relevance
“…T1D is more frequent in white populations, but its incidence varies in Caucasians from different countries and within the same country 2 . In Brazil, the estimated frequency of risk polymorphisms for T1D showed inter-regional differences and were usually lower than those in populations referred to as Caucasians in other countries 3 4 5 , reinforcing the need to expand genetic predisposition studies in the Brazilian population to clarify causal variants and related ancestry. The Brazilian population was formed by a strong admixture from three different ancestral roots, i.e., Amerindians, Europeans, and Africans, thereby hindering ethnic identification (or genetic ancestry) based predominantly on skin color 6 .…”
mentioning
confidence: 99%
“…T1D is more frequent in white populations, but its incidence varies in Caucasians from different countries and within the same country 2 . In Brazil, the estimated frequency of risk polymorphisms for T1D showed inter-regional differences and were usually lower than those in populations referred to as Caucasians in other countries 3 4 5 , reinforcing the need to expand genetic predisposition studies in the Brazilian population to clarify causal variants and related ancestry. The Brazilian population was formed by a strong admixture from three different ancestral roots, i.e., Amerindians, Europeans, and Africans, thereby hindering ethnic identification (or genetic ancestry) based predominantly on skin color 6 .…”
mentioning
confidence: 99%
“…Protein tyrosine phosphatase non-receptor type 22 (PTPN22) also serves as a negative factor on TCR signaling [12]. A number of studies have shown that several SNPs of CTLA4 and PTPN22 are associated with a number of systemic autoimmune diseases, such as rheumatoid arthritis (RA) [14,15], inflammatory bowel disease (IBD) [16,17], systemic lupus erythematosus (SLE) [18,19], ankylosing spondylitis (AS) [20,21], Graves' disease (GD) [22,23], type 1 diabetes (T1D) [24][25][26], alopecia areata [27,28] and psoriatic arthritis [29]. A number of studies have shown that several SNPs of CTLA4 and PTPN22 are associated with a number of systemic autoimmune diseases, such as rheumatoid arthritis (RA) [14,15], inflammatory bowel disease (IBD) [16,17], systemic lupus erythematosus (SLE) [18,19], ankylosing spondylitis (AS) [20,21], Graves' disease (GD) [22,23], type 1 diabetes (T1D) [24][25][26], alopecia areata [27,28] and psoriatic arthritis [29].…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that both CTLA-4 and PTPN22 play important roles in autoimmune responses [12,13]. A number of studies have shown that several SNPs of CTLA4 and PTPN22 are associated with a number of systemic autoimmune diseases, such as rheumatoid arthritis (RA) [14,15], inflammatory bowel disease (IBD) [16,17], systemic lupus erythematosus (SLE) [18,19], ankylosing spondylitis (AS) [20,21], Graves' disease (GD) [22,23], type 1 diabetes (T1D) [24][25][26], alopecia areata [27,28] and psoriatic arthritis [29]. Our previous studies have identified the association of CTLA4 and PTPN22 genetic polymorphisms with Vogt-Koyanagi-Harada (VKH) disease, a common autoimmune uveitis entity in China [30,31].…”
Section: Introductionmentioning
confidence: 99%
“…(32) Contrariando estes dados, em nosso laboratório foi verificada a diminuição da expressão dos receptores da IL21 e da IL17 em linfócitos T CD3+ e CD4+ periféricos em pacientes com DM1A de início recente, ou seja, até seis meses de diagnóstico, quando a autoimunidade ainda está ativa (8,35) . Também não observamos elevação nas concentrações séricas de IL17 e IL23 nestes pacientes quando comparados com controles normais (35) , ou polimorfismos nos genes da IL17 (8) , IL21 (35) e IL27 (36) que pudessem influir na expressão da via Th17. Por outro lado, verificamos que o haplótipo GG das variantes da IL-23 A (rs11171806 e rs2066808) conferia proteção ao DM1A (37) .…”
Section: Interleucina 17 E Seu Receptorunclassified